2018
DOI: 10.1111/asj.13028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementary desalted mother liquor as replacement of commercial salt in diet for Thai native cattle on digestibility, energy and nitrogen balance, and rumen conditions

Abstract: Four Thai native cattle were used in a 4 × 4 Latin square design experiment to evaluate the availability of desalted mother liquor (DML) as replacement of salt in concentrate. Each cattle was assigned to one of the following concentrate feeding treatments: C1, 1% NaCl was added as salt; C2, 2% NaCl was added as salt; D1, 1% NaCl was replaced by DML; D2, 2% NaCl was replaced by DML, on a dry matter (DM) basis. The animals were fed rice straw and experimental concentrates (40:60) at 1.9% of body weight on a DM b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…With regard to salinity, certain in vivo results have showed that cows that consume 0.82 kg of salt daily do not exhibit altered cellulose digestibility and gross energy efficiency compared to those in animals that ate the same diet without salt 17 . In addition, another study 18 also reported that salt has no detrimental effects on nitrogen balance, rumen fermentation, methane emissions, and energy efficiency. Due attention must be given to the heavy metal concentrations of S. fusiforme, as heavy metal accumulation in ruminants would have adverse effects on health.…”
Section: Discussionmentioning
confidence: 96%
“…With regard to salinity, certain in vivo results have showed that cows that consume 0.82 kg of salt daily do not exhibit altered cellulose digestibility and gross energy efficiency compared to those in animals that ate the same diet without salt 17 . In addition, another study 18 also reported that salt has no detrimental effects on nitrogen balance, rumen fermentation, methane emissions, and energy efficiency. Due attention must be given to the heavy metal concentrations of S. fusiforme, as heavy metal accumulation in ruminants would have adverse effects on health.…”
Section: Discussionmentioning
confidence: 96%
“…The previous study (Sato et al, 2018) suggested that desalted mother liquor (DML) increased ADFom digestibility in Thai native bulls. In the present study, however, the ML did not have the effect.…”
Section: Feed Intake Apparent Digestibility and Nitrogen And Energy Balancementioning
confidence: 99%
“…Respiration trial was conducted according to the procedure described by Sato et al (2018). Expiratory gas was collected using a ventilated hood calorimetry system as described by Suzuki et al (2008).…”
Section: Respiration Trial and Gas Analysismentioning
confidence: 99%
See 1 more Smart Citation